2021
DOI: 10.1093/pcp/pcab036
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the E2 Subunit of 2-Oxoglutarate Dehydrogenase Modulates Plant Growth by Impacting Carbon–Nitrogen Metabolism inArabidopsis thaliana

Abstract: In Arabidopsis thaliana, two genes encode the E2 subunit of the 2-oxoglutarate dehydrogenase (2-OGDH), a multimeric complex composed of three subunits. To functionally characterize the isoforms of E2 subunit, we isolated Arabidopsis mutant lines for each gene encoding the E2 subunit and performed a detailed molecular and physiological characterization of the plants under controlled growth conditions. The functional lack of expression of E2 subunit isoforms of 2-OGDH increased plant growth, reduced dark respira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 83 publications
0
6
0
Order By: Relevance
“…Interestingly, the functional lack of expression of E 2 subunit isoforms enhanced plant growth, decreased dark respiration, and reduced carbohydrate metabolism without altering the photosynthetic rate. [ 56 ] Reduction of the ODC activity via T‐DNA insertional knockout resulted in plants that exhibited a reduction of leaf total amino acids and minor changes in the levels of TCA cycle intermediates in Arabidopsis , suggesting the ODC plays a mediating role in carbon–nitrogen metabolism. [ 56 ] Similarly reducing tissue 2‐OGDH complex activity via inhibition of ODC by specific chemical inhibitors could limit respiration, as well as alter C and N metabolism demonstrating that this enzyme has an important function in nitrogen assimilation in potato tubers.…”
Section: The Organization Of the Plant Tca Cycle And Its Metabolic Co...mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the functional lack of expression of E 2 subunit isoforms enhanced plant growth, decreased dark respiration, and reduced carbohydrate metabolism without altering the photosynthetic rate. [ 56 ] Reduction of the ODC activity via T‐DNA insertional knockout resulted in plants that exhibited a reduction of leaf total amino acids and minor changes in the levels of TCA cycle intermediates in Arabidopsis , suggesting the ODC plays a mediating role in carbon–nitrogen metabolism. [ 56 ] Similarly reducing tissue 2‐OGDH complex activity via inhibition of ODC by specific chemical inhibitors could limit respiration, as well as alter C and N metabolism demonstrating that this enzyme has an important function in nitrogen assimilation in potato tubers.…”
Section: The Organization Of the Plant Tca Cycle And Its Metabolic Co...mentioning
confidence: 99%
“…[ 56 ] Reduction of the ODC activity via T‐DNA insertional knockout resulted in plants that exhibited a reduction of leaf total amino acids and minor changes in the levels of TCA cycle intermediates in Arabidopsis , suggesting the ODC plays a mediating role in carbon–nitrogen metabolism. [ 56 ] Similarly reducing tissue 2‐OGDH complex activity via inhibition of ODC by specific chemical inhibitors could limit respiration, as well as alter C and N metabolism demonstrating that this enzyme has an important function in nitrogen assimilation in potato tubers. [ 57 ] It was, moreover, suggested that the level of transcripts of the ODC genes decreased in the light or upon exposure to red light in the leaves of maize ( Zea mays L .…”
Section: The Organization Of the Plant Tca Cycle And Its Metabolic Co...mentioning
confidence: 99%
“…To further determine whether OGDH functions as part of KGDH to control floral transition, we examined loss-of-function mutants of E2 subunits. The Arabidopsis E2 subunit is encoded by two genes ( 30 ), E2a ( At5G55070 ) and E2b ( At4G26910 ), with very similar protein sequences (figs. S3A and S4, A and C).…”
Section: Kgdh Controls α-Kg Levels and Regulates Growth And Developme...mentioning
confidence: 99%
“…S3D). An e2a allele with a T-DNA insertion in its 3′ untranslated region was recently found to flower slightly later ( 30 ). We failed to obtain an e2a e2b double mutant through genetic crossing, likely due to an essential function of E2/KGDH in cellular respiration.…”
Section: Kgdh Controls α-Kg Levels and Regulates Growth And Developme...mentioning
confidence: 99%
“…The TCA cycle modulates not only the flux from 2-OG to amino acid metabolism but also the flux through 2ODDs that connects the TCA cycle with glucosinolate, flavonoid, and alkaloid formation, as well as with different reactions of amino acid and GA biosynthesis (reviewed by Araújo et al, 2014 ). The direct role of the TCA cycle in these reactions was shown through the inhibition of the mitochondrial 2-OG dehydrogenase complex ( Araújo et al, 2012a , 2012 b ; Condori-Apfata et al, 2021 ). In the mitochondrial matrix, citrate synthase controls not only the production of citrate that leads to the formation of 2-OG entering the 2ODD reactions but also the formation of products of metabolic pathways initiated by 2ODDs, e.g.…”
Section: Plant Mitochondria Are the Drivers Of 2odd Reactionsmentioning
confidence: 99%